2016
DOI: 10.1159/000446663
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Spectrum of <b><i>CYP24A1</i></b> Gene in a Cohort of Italian Patients with Idiopathic Infantile Hypercalcemia

Abstract: Background/Aims: Loss-of-function mutations in the CYP24A1 gene, which encodes the vitamin D-24 hydroxylase, have been recognized as a cause of elevated 1,25-dihydroxyvitamin D concentrations, hypercalcemia, hypercalciuria, nephrocalcinosis and nephrolithiasis in infants and adults. As only a case report describing 2 adult patients has been reported in Italian population, we report here the mutation analysis of CYP24A1 gene in an Italian cohort of 12 pediatric and adult patients with idiopathic infantile hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…It has been demonstrated that CYP24A1 knockout (-/-) mice suffer from increased sensitivity to exogenous vitamin D intake and approximately half of them die due to severe hypercalcemia [11]. In humans, CYP24A1 mutations can cause idiopathic infantile hypercalcemia (IIH) [12][13][14][15][16][17][18][19], idiopathic hypercalciuria [9], nephrocalcinosis, and possibly reduced bone density [20]. In patients with IHH due to CYP24A1 mutations, even small doses of vitamin D, as prescribed for vitamin D prophylaxis, may provoke symptomatic hypercalcemic crisis which need treatment by acute hemodiafiltration [16].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CYP24A1 knockout (-/-) mice suffer from increased sensitivity to exogenous vitamin D intake and approximately half of them die due to severe hypercalcemia [11]. In humans, CYP24A1 mutations can cause idiopathic infantile hypercalcemia (IIH) [12][13][14][15][16][17][18][19], idiopathic hypercalciuria [9], nephrocalcinosis, and possibly reduced bone density [20]. In patients with IHH due to CYP24A1 mutations, even small doses of vitamin D, as prescribed for vitamin D prophylaxis, may provoke symptomatic hypercalcemic crisis which need treatment by acute hemodiafiltration [16].…”
Section: Discussionmentioning
confidence: 99%
“…This variant within exon 6 of the CYP24A1 gene involves the highly conserved amino acid residue occurring in the polar region of the F helix: it is annotated with a very low MAF (=0.00045). Gigante et al detected this genetic variant in homozygote status in an asymptomatic child during genetic screening [82]. This Italian proband (14 years old) showed biochemical findings within the normal range: nevertheless, the putative role of this variant in a late onset manifestation of the disease or in a latent phenotype was hypothesized.…”
Section: Cyp24a1 Pathogenic Variants In Iihmentioning
confidence: 92%
“…p.Glu383Gln) and d) the protein folding (e.g. p.Glu322Lys) [2,53,82,110]. In particular, the c.476G>A (p.Arg159Gln) and the c.1186C>T (p.Arg396Trp) variants influence the heme binding site due to the destruction of the hydrogen bond between the heme propionate group and the arginine residues [110].…”
Section: Cyp24a1 Pathogenic Variants In Iihmentioning
confidence: 99%
See 2 more Smart Citations